2018
DOI: 10.1186/s13287-018-0958-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a complex skin structure via layered co-culture of keratinocytes and fibroblasts derived from induced pluripotent stem cells

Abstract: BackgroundSkin is an organ that plays an important role as a physical barrier and has many other complex functions. Skin mimetics may be useful for studying the pathophysiology of diseases in vitro and for repairing lesions in vivo. Cord blood mononuclear cells (CBMCs) have emerged as a potential cell source for regenerative medicine. Human induced pluripotent stem cells (iPSCs) derived from CBMCs have great potential for allogenic regenerative medicine. Further study is needed on skin differentiation using CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…However, to apply this approach for other autoimmune diseases and graft-versus-host disease, it will be necessary to consider using donor-matched keratinocytes, fibroblasts, and immune cells. In that case, iPSC-derived skin cells will be an important alternative to address practical difficulties in obtaining multiple tissue types from the same donor 23,50,51 . In addition, considering that other skin components, such as hair follicles 52 , vasculature 24 and adipose tissue 53 also play a role in the regulation of immune reactions in the skin, these components can be included in future constructs using recently developed tissue engineering approaches by our group 21,24 and others 54 .…”
Section: Discussionmentioning
confidence: 99%
“…However, to apply this approach for other autoimmune diseases and graft-versus-host disease, it will be necessary to consider using donor-matched keratinocytes, fibroblasts, and immune cells. In that case, iPSC-derived skin cells will be an important alternative to address practical difficulties in obtaining multiple tissue types from the same donor 23,50,51 . In addition, considering that other skin components, such as hair follicles 52 , vasculature 24 and adipose tissue 53 also play a role in the regulation of immune reactions in the skin, these components can be included in future constructs using recently developed tissue engineering approaches by our group 21,24 and others 54 .…”
Section: Discussionmentioning
confidence: 99%
“…RA was a stage-dependent agent for differentiation which directed pluripotent stem cells differentiating into ectodermal cells and upregulated K8/18 and p63 expression [37]. Therefore, RA and BMP4 play distinct but synergistic roles in promoting iPSC or ESC differentiation along the keratinocyte lineage and inhibit neural differentiation [32,38]. Additionally, studies showed that BMP4 and RA promoted the differentiation of pluripotent stem cells into the epidermal through inhibition of the canonical Wnt signaling pathway.…”
Section: Keratinocytes Derived By Bioactive Molecule Inductionmentioning
confidence: 99%
“…By 2008, several groups had adopted the technique, generating iPSCs that were considered epigenetically [44] and developmentally [45] indistinguishable from ESCs of murine [46], nonhuman primate (NHP) [47] and human origin [48,49]. To this day, pluripotent stem cell approaches to regenerative medicine have been proposed to address afflictions from cystic fibrosis [51][52][53] to diabetes [54][55][56] to third-degree burns [57][58][59]. To this day, pluripotent stem cell approaches to regenerative medicine have been proposed to address afflictions from cystic fibrosis [51][52][53] to diabetes [54][55][56] to third-degree burns [57][58][59].…”
Section: Pluripotent Cell Reprogrammingmentioning
confidence: 99%
“…Concern that cMyc would predispose iPSC-derived cells to malignant transformation was partially quashed when the TF was found to be dispensable to attain pluripotency [50]. To this day, pluripotent stem cell approaches to regenerative medicine have been proposed to address afflictions from cystic fibrosis [51][52][53] to diabetes [54][55][56] to third-degree burns [57][58][59].…”
Section: Pluripotent Cell Reprogrammingmentioning
confidence: 99%